Distance to glycemic goal at the time of treatment intensification in patients with type 2 diabetes mellitus failing metformin monotherapy in the United States. (3rd May 2020) - Fernandes, Gail; Sawhney, Baanie; Hannachi, Hakima; Liu, Jinan; Wang, Tongtong; Fu, Alex Z.; Iglay, Kristy; McNeill, Annie; Rajpathak, Swapnil
Abstract: Background: A substantial proportion of patients with type 2 diabetes mellitus (T2DM) do not reach their target HbA1c level on metformin. The objective of this retrospective observational cohort study is to better characterize the distance between HbA1c target and patient's actual HbA1c level (the distance to goal), using a target HbA1c of 7.0% (53 mmol/mol), in patients with T2DM who have started metformin monotherapy. Methods: We used data from the GE Centricity Electronic Medical Record database by IQVIA in 2016 in the United States (US) to identify adults with T2DM who started metformin monotherapy (MM) and received at least 90 days of treatment. Patients were categorized into three groups: those who achieved the goal of HbA1c <7.0%, those who did not achieve the goal of HbA1c <7.0% (i.e. failed MM) and received intensified treatment, and those who failed MM and did not receive intensified treatment. Distance to goal was computed for patients in each group. Results: We identified 20, 704 patients in the US database who started MM; 1741 (8.4%) failed MM and received intensified treatment, while 4977 (24.0%) failed MM and did not receive intensified treatment. The mean post-MM HbA1c for those who failed MM and received intensified treatment was 8.7% (72 mmol/mol) (median 8.2%, 66 mmol/mol) and the mean distance to goal was 1.7% (median 1.2%). The mean post-MM HbA1c for those who failed MM and did not receive intensified treatment was 8.0% (64 mmol/mol) (median 7.5%, 58 mmol/mol) and the mean distance to goal was 1.0% (median 0.5%). Conclusion: A proportion of US T2DM patients do not achieve glycemic control (target HbA1c < 7.0%) despite 90 days of MM. Patients who failed MM and eventually received intensified treatment did so when their HbA1c distance to goal exceeded the level at which one add-on therapy alone might be sufficient to bring them to goal.